Spectral and Thermal Studies of Transition Metal Complexes of Acetamido Benzoic Acids with Hydrazine - Helen Pricilla Bai, E.; Vairam, S. (Asian Journal of Chemistry, 2012)
The metal complexes of isomeric acetamido benzoic acids with Co, Ni, Zn and Cd metals have been prepared and characterized by analytical, spectroscopic (IR, UV reflectance), micro elemental analysis, simultaneous TG-DTA, powder XRD, magnetic susceptibility measurements and SEM-EDS studies: [Ni(2-acamb)2(N2H4)].2H2O; [M(2-acamb)2(N2H4)].H2O, where M = Co, Cd and Zn; [M(3-acamb)2(N2H4)].H2O, where M = Ni and Co and [M(3-acamb)2(N2H4)].2H2O where M = Cd and Zn; [Co(4-acamb)2(N2H4)].H2O and [M(4-acamb)2(N2H4)].2H2O where M = Ni, Cd and Zn, 2-acambH = 2-acetamido benzoic acid, 3-acambH = 3-acetamido benzoic acid and 4-acambH = 4-acetamido benzoic acid. Among them Ni, Co and Cd complexes of 2-acambH and 4-acambH were obtained at pH 5 and 6 respectively, whereas Zn complexes of both acids were formed at pH 3. 3-acambH complexes were prepared at pH 5. The IR spectra of the compounds display the N-N stretching frequency absorptions in the range of 984-926 cm-1, which reveals the bridging bidentate coordination of hydrazine. The compounds show n(C=O) (asym) values in the range 1611-1582 cm-1 and the n(C=O) (sym) values at 1555-1422 cm-1. The difference of n(C=O) (asym) and n(C=O) (sym), which is found to be 48-162 cm-1, indicates that the carboxylate anion is coordinated to the metal ion in the bidendate fashion. These complexes undergo dehydration in the range of 140-177 ºC first and then oxidative decomposition showing exotherms in the range of 200-278 ºC and in the range of 400-682 ºC to their respective metal oxides. Cadmium and zinc complexes show their intermediates as carbonates. The electronic spectra and the magnetic susceptibility values suggest that the coordination number of the complexes is 6 with distorted octahedral geometry. XRD patterns show isomorphism among the complexes with similar molecular formulae. The SEM-EDS studies reveal the presence of respective metal oxides.